Modified Venturini Modulation Method for Matrix Converter Under Unbalanced Input Voltage Conditions - Jarustus, Neerakorn; Kumsuwan, Yuttana (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
A Venturini method is one of the popular modulation techniques for controlling the matrix converter due to its simplicity of gating signal generation and a maximum voltage ratio of 0.866 between fundamental output magnitude and fundamental input magnitude. However, even with simple modulation method and achieving maximum fundamental output magnitude, the possible unbalanced conditions of the three-phase input voltages affect the reduction and distortion of the output performances. Thus, a control strategy based on Venturini method is presented in this paper, in order to solve the impacts of unbalanced input voltage conditions on the matrix converter performance. Conceptually, this strategy is done by modifying the mathematical model for controlling the modulating waves as generated in the event of normal situation. Up to this approach, it can support either singlephase condition or two-phase condition. Performance of the proposed control strategy was verified by a simplified simulation model in the MATLAB/Simulink software. It is shown that the matrix converter can be controlled by the proposed algorithm without the energy storage devices for regulating the output voltages, which results in a good steady-state and dynamic operation.